Transformasi Kurikulum Pendidikan Islam Abad ke-21: Integrasi Model Subject, Student, dan Problem-Centered dalam Kerangka Insan Kamil - Andi Qadri Al-Aqsha; Della Anjelia Saputri; Yusuf Nur Rochman Rasyid; Khuriyah Khuriyah (HIBRUL ULAMA, 2025)
This study aims to analyze the transformation of the 21st-century Islamic education curriculum through the integration of subject-centered, student-centered, and problem-centered models, to form an insan kamil with character and adaptability. This study is a descriptive qualitative study based on a literature review, which examines various scientific literature related to the basic principles and design models of curriculum development, and the integration of Islamic values within them. Data were collected through a literature review of books, journal articles, and scientific publications. Data were analyzed through data reduction, theme classification, narrative presentation, and conclusion drawing using source triangulation techniques to ensure data validity. The results indicated that an Islamic education curriculum relevant to 21st-century demands must be based on the principles of relevance, flexibility, continuity, efficiency, and effectiveness, as well as the integration of subject-centered, student-centered, and problem-centered models. The integration of these three curriculum models results in a comprehensive learning design that balances cognitive, affective, and spiritual aspects. The Islamic education curriculum must be integrative and transformative to produce an insan kamil who is tolerant, creative, and contributes positively to global civilization based on the values ??of rahmatan lil 'alamin (blessing for the universe).